Differential impact of adopting Islamic banking: A quasi-experimental approach - Adil Saleem (13822021) (2025)
This study examines the treatment effect of the adoption of Islamic banking system in Pakistan. Compared to traditional banks, the distinct involvement of Islamic banks in real trading, along with its risk-sharing attributes, necessitates an examination of whether these differences impact economic growth. We applied a novel quasi-experimental research design using the synthetic control method (SCM) to examine the incremental effect of Islamic banking adoption on economic growth from 1990 to 2022. Results confirm that the Islamic financial system contributed differentially to economic growth in Pakistan, compared to the control group (51 countries), in the post-adoption period. The counterfactual effect on economic growth is estimated to be between 23 % and 32 % compared to the countries where Sharia banking is absent. The results are consistent and robust to alternative analysis, SCM with additional covariates, and placebo tests. The results also provide crucial implications for countries and central banks to implement Sharia-based banking, complementing the United Nations’ Sustainable Development Goal 8. Other Information Published in: Research in International Business and Finance License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ribaf.2025.102793